Grounding and shielding circuits and interference - Morrison, Ralph (IEEE Press Wiley-Interscience, 2007)
The fifth edition of Grounding and Shielding has been revised throughout. Material has been added on transmission lines, radiation and printed circuit design, all of which are of great current interest because of the smaller dimensions of electronic devices.